Brain-Specific Ultrastructure of Capillary Endothelial Glycocalyx and Its Possible Contribution for Blood Brain Barrier. Issue 1 (December 2018) - Ando, Yoshiaki; Okada, Hideshi; Takemura, Genzou; Suzuki, Kodai; Takada, Chihiro; Tomita, Hiroyuki; Zaikokuji, Ryogen; Hotta, Yasuaki; Miyazaki, Nagisa; Yano, Hirohisa; Muraki, Isamu; Kuroda, Ayumi; et al.
Abstract Endothelial glycocalyx coats healthy vascular endothelium and plays an important role in vascular homeostasis. Although cerebral capillaries are categorized as continuous, as are those in the heart and lung, they likely have specific features related to their function in the blood brain barrier. To test that idea, brains, hearts and lungs from C57BL6 mice were processed with lanthanum-containing alkaline fixative, which preserves the structure of glycocalyx, and examined using scanning and transmission electron microscopy. We found that endothelial glycocalyx is present over the entire luminal surface of cerebral capillaries. The percent area physically covered by glycocalyx within the lumen of cerebral capillaries was 40.1 ± 4.5%, which is significantly more than in cardiac and pulmonary capillaries (15.1 ± 3.7% and 3.7 ± 0.3%, respectively). Upon lipopolysaccharide-induced vascular injury, the endothelial glycocalyx was reduced within cerebral capillaries, but substantial amounts remained. By contrast, cardiac and pulmonary capillaries became nearly devoid of glycocalyx. These findings suggest the denser structure of glycocalyx in the brain is associated with endothelial protection and may be an important component of the blood brain barrier.